1994
DOI: 10.1007/bf00303087
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of collagens type I, type III and type V in the pancreas of rat, dog, pig and man

Abstract: The presence of collagens type I, type III and type V was determined immunohistochemically in pancreatic tissue of rat, pig, dog and man. The reaction to anti-collagen type I is weak (pig, dog) or moderate (rat, man) in the peri-insular region and in the lobar, lobular and acinar septa, whereas the reaction to anti-collagen type III is well developed. In rat and dog, the latter reaction deposit on the lobar and acinar septa is prominent. These elements only show a moderate reaction intensity in pig and man. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…Other studies have shown that basement membrane structure and major extracellular matrix proteins are not found between islet cells (11,38,39). Within the islet, basement membrane was observed only around capillaries (21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have shown that basement membrane structure and major extracellular matrix proteins are not found between islet cells (11,38,39). Within the islet, basement membrane was observed only around capillaries (21).…”
Section: Discussionmentioning
confidence: 95%
“…A continuous periinsular extracellular matrix that contains laminin, fibronectin, and collagen types IV and V has been described in human pancreas (21,38). Other studies have shown that basement membrane structure and major extracellular matrix proteins are not found between islet cells (11,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Some findings have indicated that in the human pancreas, endocrine cells are separated from exocrine cells by reticulin fibres [15] and the endocrine-exocrine interface in different species variably appears to contain collagens I, IV, V and VI, as well as Lm [16][17][18]. Electron microscopy detected [19] a typical BM facing the endocrine cell at the endocrine-exocrine interface as a peri-islet BM, but the same study failed to detect BM inside human islets.…”
Section: Introductionmentioning
confidence: 96%
“…Donor variables include age, gender, body mass index, diet, trauma, hypoxia or ischemic conditions (11). Pancreatic architecture, composition of Clostridium histolyticum collagenase preparations, endotoxicity, digestion time and cold ischemic time are some of the variables related to the islet purification procedure (12).…”
Section: Introductionmentioning
confidence: 99%
“…ECM is found in two forms, namely, interstitial matrix and basement membrane. The pancreatic islet basement membrane is composed of collagen IV, laminin and fibronectin (12). Disruption of islet cell-matrix interactions (30-32) and loss of the basement membrane lead to induction of apoptosis (33,34).…”
Section: Introductionmentioning
confidence: 99%